Traditional games to reinforce the character of students in terms of educational qualifications: a meta-analysis - Hendra Mashuri (Universitas Nusantara PGRI Kediri, 2022)
Physical education plays an important role in shaping human character through pleasurable physical activity. One of the fun and noble physical activities is the traditional game. Traditional games are rich in noble values that are able as learners' character boosters. This study analyzed the role of traditional games on strengthening the character of learners reviewed from the level of education. The research method used is a meta-analysis by checking ten national journal articles formulated with the Glass formula. The results showed that traditional games have a very strong influence on strengthening the character of middle school education learners. At the elementary school level, traditional games have a high effect on strengthening the character of learners. But at the high school level, the influence of traditional games on strengthening the character of learners can be ignored or the effect is very small.